Identification of a Tetanus Toxin Specific Epitope in Single Amino Acid Resolution. Issue 10 (18th September 2017) - Palermo, Andrea; Weber, Laura K.; Rentschler, Simone; Isse, Awale; Sedlmayr, Martyna; Herbster, Karin; List, Volker; Hubbuch, Jürgen; Löffler, Felix F.; Nesterov‐Müller, Alexander; Breitling, Frank
Abstract : Vaccinations are among the most potent tools to fight infectious diseases. However, cross‐reactions are an ongoing problem and there is an urgent need to fully understand the mechanisms of the immune response. For the development of a methodological workflow, the linear epitopes in the immune response to the tetanus toxin is investigated in sera of 19 vaccinated Europeans applying epitope mapping with peptide arrays. The most prominent epitope, appearing in nine different sera (923 IHLVNNESSEVIVHK937 ), is investigated in a substitution analysis to identify the amino acids that are crucial for the binding of the corresponding antibody species − the antibody fingerprint. The antibody fingerprints of different individuals are compared and found to be strongly conserved (929 ExxEVIVxK937 ), which is astonishing considering the randomness of their development. Additionally, the corresponding antibody species is isolated from one serum with batch chromatography using the amino acid sequence of the identified epitope and the tetanus specificity of the isolated antibody is verified by ELISA. Studying antibody fingerprints with peptide arrays should be transferable to any kind of humoral immune response toward protein antigens. Furthermore, antibody fingerprints have shown to be highly disease‐specific and, therefore, can be employed as reliable biomarkers enabling the study of cross‐reacting antigens. Abstract : The vaccination against tetanus elicits a reliable protective immune response and, therefore, can serve as an ideal model system. In this study, the authors demonstrate the feasibility of a workflow for the detection of linear epitopes on the tetanus toxin with peptide microarrays in the resolution of single amino acids. With substitution analyses, the exact specificity of an identified antibody – the antibody fingerprint – is compared in different individuals and found to be highly conserved, which opens the exploitation of antibody fingerprints as reliable biomarkers, for the development of vaccines and the understanding of immune mechanisms.